Preparation and Characterization of Hydrophilic Wetting-Modified Polyamide Fibers - Liang Li; Shuping Liu; Rangtong Liu; Changjun Geng; Zedong Hu (Advances in Polymer Technology)
To improve the moisture absorption and air permeability of polyamide (PA) fibers, the modified fibers with porous structure were fabricated by melt spinning using polyethylene glycol (PEG) as the pore-forming agent due to its high solubility in water. The effects of pores caused by different PEG contents on the structure and properties of modified fibers were analyzed by electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and water contact angle. These results indicate that the porosity of modified fibers increases with PEG content increasing. Moreover, the formation of pores obviously affects the crystal forms of modified fibers. The alpha crystal gradually decreases and the gamma crystal increases with the porosity increasing. Furthermore, with respect to the modified fibers obtained from 47.33% PEG content, its water absorption increases from 3.78% of pure PA to 19.76% and its contact angle decreases from 116° to 85°. In addition, due to the interaction of hydrogen bond occurring between PA and PEG during the spinning process, the elongation at break, rupture work, and initial modulus of modified fibers were improved when the porosity was not more than 4.23%.